Careers Hunters Kuwait: Development of Training as A New Business Idea - Nur Fatin Nafiessa; Daisy Mui Hung Kee; Farra Shameen Lim; Basyeerah Basyeerah; Bilqis Salwa Nabila ri; Ashutosh Verma; Hussain Alajmi; Khalifa Abdulaziz Zayed; Rudresh Pandey; Majdi Anwar Quttainah (Global Academia Publisher, 2020)
Career Hunters’ consistently successful recruitment experience has made it popular among the job seekers in Kuwait. This company is a talent search company that offer jobs as well as recruitment services for its clients. Career Hunters focused on identifying, attracting, and evaluating outstanding candidates according to the requirement of its clients. Career Hunters routinely communicate with clients on a weekly basis to ensure clients’ needs are met. The paper proposes that Career Hunters could expand its operation by providing training for new talents hired for their client’s corporation.